A study of factors influencing disruptive innovation in Chinese SMEs. Issue 1 (2nd January 2017) - Chen, Jin; Zhu, Zhaohui; Zhang, Yunting
Abstract : Although around 99% of companies in China today are small- and medium-sized enterprises (SMEs), their innovative status is not optimistic, being constrained by lack of funding, size, and experience. Nevertheless, disruptive innovation provides an opportunity for SMEs to surpass the large companies. This paper analyses external and internal factors influencing disruptive innovation in SMEs, and compares those factors between low-end disruption and high-end disruption. The results of this empirical study suggest that factors influencing high-end disruptive innovation include government support, external knowledge sources, strategic support, and dominant position of R&D; while the factors influencing low-end disruptive innovation are cooperation with venture capitalists, external knowledge sources, dominant position of R&D, and entrepreneurs' innovation willingness. Two case studies are described to illustrate our results.